Current status of faculty development in under graduate medical education of Bangladesh (Bangladesh Journal of Medical Education, 2017)
This descriptive cross sectional study was carried out to determine the current status of faculty development in undergraduate medical education of Bangladesh. This study was carried out in eight (four Government and four Non- Government) medical colleges in Bangladesh over a period from July 2015 to June 2016. The present study had a semi-structured self-administered questionnaire for individual teacher. Total 181 teachers responded to the questionnaire. 56% of teachers said that faculty development activities were regularly conducted. About duration of faculty development activity 74% of teachers said it was 1-3 days duration. 42% of the teachers said faculty development activity conducted once in a week and 39% said occasional conduction of faculty development activity in their institute About the type of faculty development activity clinical meeting was commonest (65%), related to medical education (48%) and related to research (53%). About the topics of medical education related activities were teaching methodology (46%), assessment (32%). Research related activities were journal club (91%) and research methodology (67%). Faculty development activity was conducted through teachers association (53%) and medical education unit (50%). In conclusion some parts of FD activity are present in most of the colleges like clinical meeting, few medical education related session, and research related activity. For upgrading of medical education faculty development programme should be conducted regularly, monitoring of present programme and development of qualified resource person should be ensured.Bangladesh Journal of Medical Education Vol.8(2) 2017: 2-6